L-Asparaginase Exerts Neuroprotective Effects in an SH-SY5Y-A53T Model of Parkinson’s Disease by Regulating Glutamine Metabolism - Zhang, Qingxi; Gao, Yuyuan; Zhang, Jiahui; Li, You; Chen, Jianing; Huang, Rui; Ma, Guixian; Wang, Limin; Zhang, Yuhu; Nie, Kun; Wang, Lijuan (Frontiers in Molecular Neuroscience, 2020)
Background: Parkinson's disease (PD) is the second most common neurodegenerative disease worldwide and involves deficiencies in alpha-synuclein (αSyn) degradation. Effective therapeutic strategies for PD are urgently needed. L-asparaginase (L-ASNase) has been developed for therapeutic applications in many fields because it catalyzes the hydrolysis of asparagine and glutamine in cancer cells, which may also activate autophagy and induce the degradation of accumulated αSyn. However, the efficacy and related mechanism of L-ASNase in PD remain poorly understood. Methods: We determined the correlation between L-ASNas and autophagic degradation of αSyn in a cell model of PD. Mitochondrial function and apoptosis were examined in the presence or absence of L-ASNase. Then, we applied GC-MS/MS targeted amino acid metabolomics analysis to validate the amino acid regulation induced by L-ASNase treatment. Glutamine was added to verify whether the neuroprotective effect was induced by deprivation of glutamine. αSyn-related autophagy and mitochondrial fusion/fission dynamics were detected to explore the mechanism of L-ASNase -based therapy in PD. Results: L-ASNase activated the autophagic degradation of αSyn in a cell model of PD without cytotoxicity at specific concentrations/times. Under these conditions, L-ASNase showed substantial neuroprotective effects, including improvements in mitochondrial function and decreased apoptosis. Through GC-MS/MS targeted analysis, glutamine metabolism was identified as the target of L-ASNase in PD treatment, and the neuroprotective effect of L-ASNase was reduced after glutamine supplementation. Conclusions: Our study demonstrated for the first time that L-ASNase had a neuroprotective effect on a cell model of PD through a moderate deprivation of glutamine, which induced autophagic activation and mitochondrial fusion. Therefore, we demonstrated that L-ASNase could be a promising and effective drug for PD treatment.